Characterization of periodontal fibroblast spheroids in vitro, interaction with 3d membranes and potential for tissue regeneration - Berahim, Zurairah (Universiti Sains Malaysia, 2012)
Autologous transplantation of periodontal fibroblasts may be a promising technique to induce tissue regeneration In the treatment of periodontal disease. Spheroid culture is a form of three dimensional cell culture that promotes cellmatrix interaction and cellular differentiation without recourse to exogenous growth factors. The aim of this study was to develop 3D spheroidal cultures of periodontal fibroblasts In vitro and characterize them with respect to their potential use in periodontal tissue repair and rege09!"8tion. In this study commercial normal periodontal fibroblasts were grown in spheroidal form In vitro using the liquid overlay technique. The fibroblast spheroids were characterized by histology, DNA quantification, scanning electron microscopy and immunohistochemistry. Over 14 days, periodontal fibroblasts formed viable spheroids which Incorporated an extracellular matrix rich in collagen type I and periostln. Production of cementum attachment protein which is a marker of dental hard tissue formation, was not detected. This study shows that periodontal fibroblast spheroids may have the potential to be used as an adjunct for periodontal regeneration.